Historical aspects and current status of the application of DRT in Ukraine and the World - Moskaliuk, Nadiia; Sloma, Valentyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
Nowadays, more and more scientific discussions arise in the field of legal, medical and moral aspects of the use of assisted reproductive technologies (ART). The latest discoveries in the field of medicine have a significant impact on the idea of the legal status and life of a person. In particular, a person’s right to reproductive health is part of the right to health care and personal non-property rights. Currently, the issue of legal regulation of human reproduction is gaining special relevance. Evidence of this is the appearance of the concept of "reproductive rights" in international documents and scientific literature. This issue is of primary importance today in the world and in Ukraine, because, as is known, in recent years there has been a trend towards a decrease in the population, an increase in mortality (caused by epidemics, wars, natural disasters, etc.) and a decrease in the birth rate. The main purpose of a person’s reproductive rights is to ensure the possibility of his reproduction. After all, this property is an important characteristic of a person’s right to life. This is confirmed by the fact that reproduction affects the quality of human life and the possibility of procreation. Unfortunately, today the legislator does not give definitions of human reproductive rights and does not disclose their specific features. Postmortem reproduction (conception and birth) of a child already after the death of one or both parents is not a fantasy in our time, but the result of the use of DRT. Therefore, the legal and bioethical problems of the use of DRT are the subject of lively discussions among scientists and medical professionals and require proper legal regulation both in Ukraine and in many countries of the world. The purpose of the article is to find out the historical prerequisites and the current state of the use of DRT in Ukraine and the world, the peculiarities and problems of legal regulation of this issue, and ways to solve them.